2017
DOI: 10.1093/treephys/tpx142
|View full text |Cite
|
Sign up to set email alerts
|

Does winter desiccation account for seasonal increases in supercooling capacity of Norway spruce bud primordia?

Abstract: Bud primordia of Picea abies (L.) H. Karst. remain ice free at subzero temperatures by supercooling. Once ice forms inside the primordium, it is immediately injured. Supercooling capacity increases seasonally from ~−5 °C to as much as −50 °C by currently unknown mechanisms. Among other prerequisites, dehydration of tissues over the winter months has been considered to play a key role in freezing tolerance. In this regard, the water content of bud primordia may be crucial, especially in reference to supercoolin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…Strikingly, the extent of freeze dehydration appeared not much different to that found in P. abies where buds finally get frost damaged by intracellular freezing when they cannot retain their deeply supercooled state (Kuprian et al, 2017). However, only recently it was shown that low midwinter MPa values of P. abies bud tissues have no effect on their supercooling capacity (Kuprian, Munkler, Resnyak, & Neuner, 2018). From these findings, the functional involvement of freeze dehydration or at least a dose-effect relationship between freeze dehydration and freezing resistance of buds is not so clear.…”
mentioning
confidence: 72%
See 4 more Smart Citations
“…Strikingly, the extent of freeze dehydration appeared not much different to that found in P. abies where buds finally get frost damaged by intracellular freezing when they cannot retain their deeply supercooled state (Kuprian et al, 2017). However, only recently it was shown that low midwinter MPa values of P. abies bud tissues have no effect on their supercooling capacity (Kuprian, Munkler, Resnyak, & Neuner, 2018). From these findings, the functional involvement of freeze dehydration or at least a dose-effect relationship between freeze dehydration and freezing resistance of buds is not so clear.…”
mentioning
confidence: 72%
“…alnobetula are suggested to either belong to Type I or II supercooling buds. Type III can be excluded, as these buds after supercooling would show intracellular freezing upon frost damage (Kuprian et al, ; Kuprian et al, ; Rajashekar & Burke, ), which, using DTA and IDTA, could be demonstrated is not the case for buds of A . alnobetula .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations